Detection of Pancreatic Cancer-induced Cachexia using a Fluorescent Myoblast Reporter System and Analysis of Metabolite Abundance - Winnard, Paul T. (Cancer Res, 2015)
The dire effects of cancer-induced cachexia undermine treatment and contribute to decreased survival rates. Therapeutic options for this syndrome are limited, and therefore efforts to identify signs of precachexia in cancer patients are necessary for early intervention. The applications of molecular and functional imaging that would enable a whole-body “holistic” approach to this problem may lead to new insights and advances for diagnosis and treatment of this syndrome. Here we have developed a myoblast optical reporter system with the purpose of identifying early cachectic events. We generated a myoblast cell line expressing a dual tdTomato:GFP construct that was grafted onto the muscle of mice bearing human pancreatic cancer xenografts to provide noninvasive live imaging of events associated with cancer-induced cachexia (i.e., weight loss). Real time optical imaging detected a strong tdTomato fluorescent signal from skeletal muscle grafts in mice with weight loses of only 1.2 to 2.7% and tumor burdens of only ~79 to ~170 mm(3). Weight loss in cachectic animals was also associated with a depletion of lipid, cholesterol, valine, and alanine levels, which may provide informative biomarkers of cachexia. Taken together, our findings demonstrate the utility of a reporter system that is capable of tracking tumor-induced weight loss, an early marker of cachexia. Future studies incorporating resected tissue from human pancreatic ductal adenocarcinoma (PDAC) into a reporter-carrying mouse may be able to provide a risk assessment of cachexia with possible implications for therapeutic development.